216k views
2 votes
I have absolutely no clue how to solve this PLEASE HELP.

I'm suppose to factor this... but how??
x(2y-x)^2 + 2x^2 (x-2y)

1 Answer

2 votes

Answer:


=x(2y-x)(2y-3x)

Explanation:

We want to factor the following expression:


x(2y-x)^2+2x^2(x-2y)

First, notice that both of the terms have an x. Thus, let's factor out the x first:


=x((2y-x)^2+2x(x-2y))

Now, notice the similarity between (2y-x) and (x-2y). If we multiply either of them by a negative, they will be the same.

Therefore, we can factor out a negative from (x-2y). This will give us:


=x((2y-x)^2+2x(-(2y-x))

Since multiplication is commutative:


=x((2y-x)^2-2x(2y-x))

Now, we can factor out the (2y-x):


=x(2y-x)((2y-x)-2x)

And we can simplify this to get:


=x(2y-x)(2y-3x)

Alternate Method:

Starting from here:


x((2y-x)^2+2x(x-2y))

We can factor out a negative from the (2y-x)² term. This yields:


=x((-1(x-2y))^2+2x(x-2y))

Since -1 squared is positive, we can simplify:


=x((x-2y)^2+2x(x-2y))

Now, we can factor out the (x-2y):


=x(x-2y)((x-2y)+2x)

Simplifying gives:


=x(x-2y)(3x-2y)

While this looks different, they are exactly the same. If we factor out a negative from both the second and third term, we get:


=x(-(2y-x))(-(2y-3x))

The negatives will cancel, leaving us with:


=x(2y-x)(2y-3x)

This is exactly the same as what we acquired previously.

Therefore, both answers are correct.

User Ferrarezi
by
4.6k points